Comparative study of nanoparticles and alcoholic fuel additives with optimized synthesis of palm-sesame biodiesel using tribological and internal combustion engine testing / Muhammad Mujtaba Abbas - Muhammad Mujtaba , Abbas (2021)
The demand for renewable energy is steadily increasing due to the rise in population, economic development, and environmental issue globally. Renewable energy sources are now considered better replacements for fossil fuels. Meanwhile, up to 20% of liquid fuels such as methyl esters are currently being blended with petroleum fuels. Recently, the commercialization of biodiesel is a significant challenge due to its poor cold flow properties and oxidative stability. Poor cold flow properties and oxidative stability can be improved by selecting suitable vegetable oils for producing different blends. Among all available vegetable oils, sesame seed oil (SSO) has unique cold flow properties and oxidation stability. This research aimed to improve the cold flow, lubricity, and diesel engine characteristics of biodiesel produced from the palm-sesame oil blends. Response Surface Methodology (RSM) and Extreme Learning Machine (ELM) techniques were used to develop the production process, and the input variables (time, catalyst amount, methanol to oil ratio, and duty cycle) were optimized. The optimum yield of P50S50 (50% palm + 50% sesame) biodiesel obtained was 96.61 % under operating parameters such as time (38.96 min), duty cycle (59.52 %), methanol to oil ratio (60 V/V %), and catalyst amount (0.70 wt.%). The cold flow characteristics of P50S50 biodiesel were significantly improved, such as cloud point (7.89 ℃), pour point (3.80 ℃), and cold filter plugging point (− 1.77 ℃) with better oxidation stability of 6.89 h. During the test run, the friction coefficient was measured directly using the high-frequency reciprocating rig (HFRR). The results exhibited that B10 (Malaysian commercial diesel) demonstrated a poor coefficient of friction and wear scar diameter compared with other tested fuels. The addition of ethanol as a fuel additive in the B30 fuel sample reduced fuel lubricity and increased the wear and friction coefficient compared with other fuel additives. B30 fuel with titanium oxide (TiO2) nanoparticles exhibited improved results with the minimum wear scar diameter and lowest friction coefficient among all other fuel samples. Dilution of engine oil with unburned fuels changes its lubricity and tribological properties. Lubricating oil diluted with B10 showed a high coefficient of friction (COF) with severe abrasive and adhesive wear compared with mineral lubricant, among other fuels. Lubricant+B30+TiO2 showed the minimum increase in COF value among all other modified fuels compared to SAE-40 mineral lubricant. Engine performance and emissions characteristics were studied using a compression ignition (CI) diesel engine with variable engine rpm at full load conditions. The results were compared with B30 and B10 fuels. The main findings indicated that the B30+TiO2 ternary blend showed an overall decrease in brake-specific fuel consumption compared with other tested fuels. B30+DMC produced higher brake thermal efficiency, among other fuels. B30+DMC ternary blend showed a reduction in carbon monoxide (CO) and hydrocarbons (HC) emissions compared to B30. B30+CNT ternary blend showed a slight decrease in nitrogen oxide (NOx) emissions compared to B30. The research suggests that Palm-Sesame biodiesel with fuel additives is a suitable replacement for diesel fuel in compression ignition engines without engine modification.